Pengembangan Website Keuangan dan Stok Barang Pada Toko Nextsports.Id Kebumen - Aziz Lukmanudin; Endang Wahyuningsih (Applied Information Technology and Computer Science (AICOMS), 2026)
Manual stock management and financial recording in Micro, Small, and Medium Enterprises (MSMEs) often cause recording errors, stock inconsistencies, and delays in report preparation. Similar problems occurred at NextSports.id Kebumen, which still managed stock and transactions separately. This study aimed to develop an integrated web-based stock and financial management information system to improve operational effectiveness and data consistency. The research used the Research and Development (R&D) method with the Agile development model. The system was developed using PHP Native and MySQL. Functional testing was conducted using Black Box Testing, while usability evaluation used the System Usability Scale (SUS). The results showed that all main system functions operated properly according to user requirements. The SUS evaluation produced an average score of 81.5, indicating that the system had an acceptable usability level and could assist users in managing stock and financial data more effectively and efficiently.